Digital Technology and the Responsibility of French Legal Professionals (TEST BioLaw Journal - Rivista di BioDiritto, 2026)
The individual responsibility of legal professionals plays a key role in building trust with their clients. The increasing number of digital tools available to them is changing their daily practices, making many tasks simpler and quicker. However, this also raises questions about the legitimacy of their involvement, given that complementarity can also become competition. Applying the prism of civil liability to the duty to advise and the technical diligence expected of legal professionals provides a way of addressing this issue as it evolves.